2017
DOI: 10.1186/s41021-016-0066-4
|View full text |Cite
|
Sign up to set email alerts
|

Genetic polymorphisms of human cytochrome P450 CYP1A1 in an Egyptian population and tobacco-induced lung cancer

Abstract: BackgroundCytochrome P450 CYP1A1 helps detoxify the potential carcinogens in tobacco smoke, it was reported that polymorphisms in the coding gene result in variation in the expression and activity levels which alter metabolism and clearance of carcinogens and therefore modify cancer risk. In this work, we aimed to identify CYP1A1 gene polymorphisms associated with lung cancer in Egyptian population and to examine the interaction effect with Tobacco smoking in modulating disease risk.MethodsA case–control study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 35 publications
(39 reference statements)
1
10
0
1
Order By: Relevance
“…The role of CYP1A1 polymorphisms in breast cancer risk in individuals, however, has been conflicting. Some studies have shown that CYP1A1 polymorphisms are significantly associated with breast cancer risk ( 13 , 34 , 36 ) consistent with this study. In this study, patients with either G or C allele carriers were approximately equally susceptible to breast cancer and the G and C allele carriers were under represented in the control group.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The role of CYP1A1 polymorphisms in breast cancer risk in individuals, however, has been conflicting. Some studies have shown that CYP1A1 polymorphisms are significantly associated with breast cancer risk ( 13 , 34 , 36 ) consistent with this study. In this study, patients with either G or C allele carriers were approximately equally susceptible to breast cancer and the G and C allele carriers were under represented in the control group.…”
Section: Discussionsupporting
confidence: 92%
“…The polymorphism was evident in many different race and ethnic groups as in African-American ( 10 , 12 , 15 ), Chinese ( 14 , 16 ), Siberians ( 17 ), Canadians ( 19 ), Kashmiri and northern Indians ( 30 , 33 ), Hispanic-non-Hispanic white women ( 32 ), Egyptian Arabs [Ref. ( 34 ) and this study], and Japanese ( 35 ). On the other hand, the TT and AA wild homozygous genotypes as well as T and A allele frequencies were significantly higher among the control group which became more prevalent among smoking women with breast cancer.…”
Section: Discussionmentioning
confidence: 65%
“…As for m4 polymorphism, possible associations have been documented between the A allele and risk for lung cancer (Gallegos-Arreola et al, 2008;Shah et al, 2008;Ezzeldin et al, 2017), laryngeal squamous cell carcinoma (Gajecka et al, 2005) and thyroid cancer (Siraj et al, 2008). No association has been observed between m4 polymorphism and breast, colorectal, and gastric cancer (Li et al, 2004;Singh et al, 2007;Amrani et al, 2016, Little et al, 2006Agudo et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…A case-control study was conducted that included 150 unrelated adult patients with primary lung cancer and 150 unrelated controls. The case series consisted of patients presented to NCI details of which have been described elsewhere [ 31 ]. Almost half of the patients seen at NCI-Cairo came from the Cairo metropolitan area, whereas the rest of the patients were from other regions in South and North Egypt.…”
Section: Methodsmentioning
confidence: 99%